2018
DOI: 10.1111/jcmm.13817
|View full text |Cite
|
Sign up to set email alerts
|

LncRNARMRP promotes nucleus pulposus cell proliferation through regulating miR‐206 expression

Abstract: Long noncoding RNAs (LncRNAs) are involved in the pathogenesis of intervertebral disc degeneration (IDD). However, the biological function and expression of RMRP were still unclear. In our study, we showed that RMRP expression was up‐regulated in degenerated NP tissues compared to normal NP samples, and higher RMRP expression was associated with the disc degeneration grade. Further studies indicated that ectopic expression of RMRP enhanced NP cell growth and also enhanced the expression of ki‐67, PCNA and cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“… 36 RMRP has also been indicated to promote cell proliferation of nucleus pulposus by regulating miR-206 expression. 37 Likewise, in our study, we also found that RMRP can directly bind with miR-206. Subsequently, we innovatively identified that DDX5 is a direct target of miR-206 and that its expression is inhibited by miR-206.…”
Section: Discussionsupporting
confidence: 80%
“… 36 RMRP has also been indicated to promote cell proliferation of nucleus pulposus by regulating miR-206 expression. 37 Likewise, in our study, we also found that RMRP can directly bind with miR-206. Subsequently, we innovatively identified that DDX5 is a direct target of miR-206 and that its expression is inhibited by miR-206.…”
Section: Discussionsupporting
confidence: 80%
“…SNHG1 promotes NP cell proliferation via sponging miR-326, and downregulated miR-326 disinhibits NP cell proliferation by inactivating PCNA and cyclin D1 expression. Similarly, RP11-296A18.3/miR-138/HIF1A, RMRP/miR-206/PCNA, H19/miR-22/LEF1/Wnt/β-catenin signaling, and HCG18/miR-146a-5p/TRAF6/NF-κB axis can also increase or decrease the level of proliferation, respectively [ 10 , 25 , 106 108 ]. Targeting extracellular signal-regulated kinase (Erk) and miR-146a-5p/TRAF6/NF-κB axis, respectively, lncRNA FAF1 and HCG18 modulate the ratio of synthesis-phase cells among all the cells in NP tissue [ 109 ].…”
Section: The Regulatory Mechanism Of Lncrnas In Iddmentioning
confidence: 99%
“…Owing to that, we established the coding-noncoding SuperSeries Datasets as GSE67567 in human IDD, including lncRNAs, mRNAs, and circRNAs, and miRNAs datasets as GSE19943, GSE63492, GSE56081, and GSE67566, as well as studies from other investigators (Table 1 ). Given the scarcity of studies summarizing the research progress of ncRNAs in IDD, we designed and conducted a review across the published papers [ 13 , 17 , 18 , 20 25 ]. In the current work, the state-of-art research advance and therapeutic potentials concerning the regulatory roles of miRNAs/circRNAs/lncRNAs in degenerated discs of human or animal models were summarized and discussed (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the role of RMRP in numerous cancer types, including lung cancer (8), gastric cancer (9) and glioma (10). Furthermore, Wang et al (11) demonstrated that higher RMRP expression in nucleus pulposus tissues was associated with disc degeneration grade. Another study has indicated that RMRP overexpression increased nucleus pulposus cell growth and regulated ECM expression by targeting miR-206 (11).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Wang et al (11) demonstrated that higher RMRP expression in nucleus pulposus tissues was associated with disc degeneration grade. Another study has indicated that RMRP overexpression increased nucleus pulposus cell growth and regulated ECM expression by targeting miR-206 (11). Recently, Greco et al (12) profiled the expression of 83 lncRNAs, which are known to be associated with numerous human diseases, in the left ventricle biopsies of patients with heart failure and demonstrated that RMRP was significantly upregulated in these patients.…”
Section: Introductionmentioning
confidence: 99%